Subclinical inflammation markers and their impact on obstetric outcomes in abortus imminens: A case-control study - Başkıran, Yusuf; Uçkan, Kazım; Çeleğen, İzzet (Annals of Medical Research, 2023)
Aim: The aim of the study is to investigate the relationship of subclinical inflammatory factors Platelet crit (PCT), Neutrophil-lymphocyte ratio (NLR), Monocyte-lymphocyte ratio (MLR), Platelet-lymphocyte ratio (PLR) obtained from complete blood count (CBC) with Abortion Immunes (AI) and obstetric results. In recent years, studies reveal that subclinical inflammatory markers can be used as an indicator of the inflammatory process in many diseases. Few studies have evaluated indicators of inflammation and postpartum outcomes in abortion imminent patients. Material and Methods: The study was conducted between January 2020 and January 2021. A total of 429 pregnant women, 203 of whom were pregnant with AI and 226 who were healthy, were included in the study. Results: PCT, NLR, and MLR values were significantly higher and PLR values were low in the AI group (p<0.05). PCT > 0.22, NLR > 2.29, and MLR > 0.20 were significantly associated with an increased risk of AI (P<0.05). PLR value above 135.5 was associated with the normal group. There was a significant difference between the group whose pregnancy was terminated by abortion and the group who gave birth in terms of PCT, NLR, MLR, and PLR values. PCT, NLR, and MLR values were high in the abortion group, and PLR values were low (p<0.05). Premature birth was developed in 11.3% (n=15) of AI patients. There was a significant difference between the preterm and term pregnancy in terms of PCT, NLR, MLR, and PLR levels (p<0.005). PCT, NLR, and MLR values were high and PLR levels were low in pregnant women who gave birth prematurely. Conclusion: We think that close follow-up of abortion imminent patients with high levels of these inflammatory factors is appropriate.